CONTROL PACKAGE AND TEACHING QUALITY IN NIGERIAN POLYTECHNICS - Abdulfatai Olanrewaju NURUDEEN; Adekunle Temitope MABADEJE (Malete Journal of Accounting and Finance, 2025)
The incessant report of abysmal teaching quality in Nigeria polytechnics necessitate the appraisal of the management control system in place in this public higher institute of learning. The study examine the effect of control packages on the teaching quality of polytechnics in Nigeria. The study adopt a survey research design. Data were obtained from 169 respondents through structured questionnaires. Multiple regression analysis was employed and the study revealed that administrative control (β = -0.311; p < 0.000) was found with significant negative effect; cybernetic controls (β = 0.758; p < 0.000) have a notable and positive effect while the rewards and compensations control (β = -0.047; p > 0.353) was found with negligible and negative effects on the quality of teaching in Nigeria public polytechnics. The study concludes that effective control element such as administrative, reward and compensation, and cybernetics controls improved the utilization of the resource and ensure attainment of optimum performance. The study recommends the Nigeria polytechnics managements should implement efficient policies and procedure, effective renumerations, and accurate financial and non-financial metrics in attempt to improve their performance and able to compete with foreign counterpart.